Frekuensi konsumsi growol berhubungan dengan angka kejadian diare di Puskesmas Galur II Kecamatan Galur Kabupaten Kulonprogo Provinsi DIY - Anastasia Eni R; Lily Arsanti Lestari; Muhammad Juffrie (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Diarrhea is a serious health problem in developing countries because 25% of total mortality rate among children in the world is caused by diarrhea and has caused 3-4 million of children to die annually. In Indonesia diarrhea is also a major health problem whereby morbidity rate of diarrhea in 2004 was still relatively high, i.e. 280/1000 population and the second cause of death in underfies. At the working area of Galur II Health Center mortality rate caused by diarrhea in 2007 increased from none to 2 deaths in underfies (3.14/1000) and diarrhea was in the fist rank of 10 major diseases in inpatient service activities. One cause of diarrhea is imbalance of intestinal microbes in the digestive tract. This is due to two groups of bacteria (harmful and useful/probiotic bacteria) that kill each other. Previous studies on the potential of probiotic show that Lactobacillus rhamnosus GG was effective in preventing diarrhea and shortening the duration of diarrhea. Growol contains Lactobacillus case subsp. Rhamnosus TGR 2 that has the potential as probiotic.Objective: To identify association between frequency of growol consumption and the prevalence of diarrhea.Method: The study was observational with cross sectional design carried out at the area of Galur II Health Center, Subdistrict of Galur, District of Kulonprogo, Province of Yogyakarta Special Territory. Population of the study were children of 1-5 years old with criteria willing to be studied, were not malnourished and came for weighing at Posyandu (integrated service post) in November 2008. Data collected were analyzed using linear regression test at significance 95% and descriptively.Result: Out of 472 underfies, 244 (52%) were boys and 228 (48%) girls; 22.4% had diarrhea and 77.54% had never had diarrhea; 160 consumed growol and 12 of them (7.5%) had diarrhea; 312 did not consume growol and 94 of them (30.52%) had diarrhea. Respondents consumed growol in average 3.8 times/week. There was association between frequency of growol consumption and the prevalence of diarrhea according to the equivalent Y=0.474-0.079 X or growol could prevent diarrhea if consumed minimum 6.4 times/week.Conclusion: There was association between frequency signifiant relationship between growol frequency consumption and diarrhea rate.